(untitled) (Journal of Asian Development Studies, 2025)
The study employs constructivism theory, framing theory, the Global Environmental Governance (GEG) notion, and Soft Power paradigms, with particular attention paid to resilience after the disastrous floods in 2022. Data on Pakistan’s digital diplomacy discourse were analyzed using multi-source materials, focusing on official speeches, UN interventions, and national and transnational media releases. The analysis examined how these issues were handled, particularly digital diplomacy, and how Pakistan frames, accounts for, and projects its vulnerability to climate. Framing the post-flood diplomatic activity of Pakistan in terms of an existential crisis highlights the issue of climate change. This is made through historical injustice and soft power, consequently giving it a voice for the whole (Global South). The constructivist frameworks use it to gain insight into the relationship between national identity and global norms, creating shared meanings in diplomatic practice through frames of loss, resilience, and climate justice. The research significantly employs the concept of disassociation to demonstrate the involvement of the Pakistani government with world governing institutions and climate subsidy systems concerning GEG structures. This is asserted as a contradiction between assessments of alignment, aspiration rhetoric, and the alternative marginality state of affairs. It serves as a new tool for enhancing narrative treatment change amid international interest groups. This research, therefore, transforms the understanding of climate diplomacy as an image and habits of discourse, both in terms of the impoundment of political communication and international relations in environmental governance. To an even greater degree, it introduced how this influenced the implementation of communication approaches within the imbalanced global climate dialogue and the inequitable trade agreements made by nations concerning climate change.